2019
DOI: 10.1080/17597269.2019.1628481
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of waste bio-oil as an alternate source of renewable fuel for marine engines

Abstract: Several physical and chemical properties of waste fish oils (FOs) and used cooking oils (UCOs) were of acceptable levels for utilization as renewable fuels in marine engines. However, the relatively high acid number of FOs and its increase with ageing might lead to increased risk of corrosion. The physical properties density, dynamic viscosity and kinematic viscosity, as well as water content were measured using different standard methods. Similarly, the acid number, the content of unsaturated fatty acids and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Compositional analysis of the COref was also performed using GC-FID and GC-MS. The result indicated that the sample mainly composed of aliphatic hydrocarbons predominantly composed of linear saturated hydrocarbons up to C30 with the largest compounds in the C14 to the C26 range [16]. Detailed oil composition results can be found in Tables S1 and S2.…”
Section: Oil Compositionmentioning
confidence: 99%
See 3 more Smart Citations
“…Compositional analysis of the COref was also performed using GC-FID and GC-MS. The result indicated that the sample mainly composed of aliphatic hydrocarbons predominantly composed of linear saturated hydrocarbons up to C30 with the largest compounds in the C14 to the C26 range [16]. Detailed oil composition results can be found in Tables S1 and S2.…”
Section: Oil Compositionmentioning
confidence: 99%
“…High water content and acidity in bio-oils can substantially increase the risk of corrosion during the storage and the use of the oils [21][22][23]. Moreover, the presence of water in a bio-oil decreases the heating value of the oil [16]. The measured physicochemical properties of the bio-oils are summarized in Table 1.…”
Section: Physicochemical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous works, the chemical, physical, and thermal properties and the effect of storage time on the corrosivity of bio-oils were investigated [13,26,27]. The corrosiveness of different bio-oils during storage and usage are some of the concerns yet to be investigated for addressing compatibility issues.…”
Section: Introductionmentioning
confidence: 99%